In the long run we are all herd: On the nature and outcomes of the beauty contest - Lorenzo Esposito; Giuseppe Mastromatteo (Levy Economics Institute of Bard College, 2020)
Since the 2008 crisis, the economics literature has shown a renewed interest in Keynes's "beauty contest" (BC) as a fundamental aspect of the functioning of financial markets. We argue that to understand the importance of the BC, psychological and informational factors are of small importance, and a dynamic-structural approach should be followed instead: the BC framework is paramount because it is rooted in the historical trajectory of capitalism and it is not simply a consequence of "irrational" (i.e., biased) agents. In this genuine form, the BC mechanism allows one to understand the main trends of a financialized world. Moreover, the conventional nature of financial markets provides a sound method for assessing different economic policies whose effectiveness depends on how much they can influence the convention itself. This alternative understanding of the BC can be used to start the needed rethinking of economics, urged by the crisis, that is for now reduced to studying the financial and psychological "imperfections" of the market.
Keywords: B15; E12; G01; G40; 330; Financial Crisis; Financialization; Behavioral Economics; Herd Behavior; Convention